Dana Industri Kreatif Negara : Industri Animasi Malaysia - Rafika Safa, binti Safaruddin. (Universiti Malaysia Sarawak (UNIMAS), 2015)
The study on the management ofa company in Malaysia that animation has secured fimding ofCreative Industries and the State to continue to compete in the market for animation Malaysia and overseas market. Creative Indusny in Malaysia include three main categories Multimedia Creative Industries involving the production of film and television, advertising, design, animation and digital content. In addition, other categories within the framework of the creative industry in Malaysia is the Creative Industries Cultllre covering the areas of crafts, visual arts, music, performing arts, creative writing and textiles and fashion. In addition, other categories involved are the Creative Industries Cultural Heritage, which encompasses museums, archives, restoration and cOnservation as well as other supporting industries related to distribution and marketing. This research was conducted lIsing qualitative methods as a whole.